Association between bullying and major depressive disorder in a psychiatric consultation - Perales Blum, Laurencia; Juárez Treviño, Myrthala; Capetillo Ventura, Nelly Cecilia; Rodríguez Gutiérrez, G.; Valdés Adamchik, Miguel; Treviño Treviño, J. O.; Cáceres Vargas, Mario Hernando (UANL. Facultad de Medicina, 2015)
Assess if there is a significant association between being bullied and presenting depressive symptoms. Materials and methods: In the March---October period of the present year, 8---16-year-old children and adolescents that attended psychiatric consultation for the first time in Dr. Eleuterio González Hospital were included in this study. Test Bull-S was used to determine the presence of bullying (Victim subtype); to evaluate depression 2 instruments were used according to age: Children’s Depression Rating Scale-Revised (CDRS-R) for 8---12-year olds and the Birleson Depression Self-Rating Scale (DSRS) for 13---16-year olds. A total of 147 clinical patients were studied (73 women and 74 men). Data were captured in excel and the Statistical Package for the Social Sciences (SPSS) program was used for statistical analysis. Results: A very significant association was found between being bullied and presenting depression (X2 = .289, p = .0004). Conclusions: These data are in agreement with national and international studies, therefore, reinforcing the evidence of such association. This is why we suggest inquiring about bullying in children and adolescents whose chief complaint is depressive symptomatology